Type II diabetes mellitus associated with lifestyles in the Lodana health center - Cedeño, Brenda M.; Cedeño, Danna M.; Rojas, Ondy N.; Ponluisa, Adrián W.; Chonillo, Víctor A.; Saldarriaga, William K. (Revista Gregoriana de Ciencias de la Salud, 2024)
The study aimed to examine the relationship between lifestyle and type II diabetes mellitus (DM2) in the population of Lodana, Ecuador, highlighting the importance of this analysis due to the high prevalence of the disease in the region. Through an observational and cross-sectional approach, various factors were investigated, such as eating habits, physical activity, and other risk factors in individuals over 18 years old diagnosed with DM2. Data collection methods included questionnaires, personal interviews, and specific clinical tests, providing a detailed overview of the situation. Results showed that although 60 % of participants followed adequate dietary practices, significant issues persisted regarding lack of physical activity and tobacco consumption. Additionally, economic and geographical barriers were identified, limiting access to essential healthcare services for disease management. The study pointed out the importance of improving health education and promoting healthier lifestyles, suggesting that implementing telemedicine could be an effective solution to overcome access barriers in rural areas.